Buffering effect of suspended particulate matter on phosphorus cycling during transport from rivers to lakes. (1st June 2022) - Ji, Ningning; Liu, Yong; Wang, Shengrui; Wu, Zhihao; Li, Hong
Highlights: P species shifted from TDP dominated in Miju River to TPP dominated in Lake Erhai. SPM as a sink in rivers and a source in lakes buffered P level during the wet season. P-buffering effect of SPM was associated with the quality and quantity of SPM. Increased phyto-SPM enhanced P buffering to maintain algae bloom under DIP-limitation. For water management, the inner loop among algae-SPM-P should not be ignored. Abstract: How to maintain harmful algal blooms under phosphate-limitation is still an open question in mesotrophic/eutrophic lakes. Little evidence for the importance of suspended particulate matter (SPM) in mediating phosphorus cycling and contributing to eutrophication has been generated for aquatic ecosystems, especially in coupled river-lake systems. In this study, we examined phosphorus transport and redistribution in a river-lake system in the Lake Erhai basin by establishing the relations between phosphorus distribution and phosphorus sorption behavior on SPM, and predicted how changes in the quality and quantity of SPM might influence phosphorus cycling by laboratory experiments and modeling. During the wet seasons, TP pool shifted from being dominated by total dissolved phosphorus (TDP) in the Miju River and estuary regions (73±5%) to being dominated by total particulate phosphorus (TPP) (74±11%) in Lake Erhai. The detritus-SPM in the Miju River as a P-sink and phytoplankton-SPM in Lake Erhai as a P-source buffered TDP levels during the wet seasons, which attributed to P activity and phytoplankton-POC of SPM. Increasing SPM concentrations could enhance the P-buffering. When C0 ≤ 5 μmol/L and phytoplankton-SPM ≥ 16 mg/L, P release increased by 50%-300%; when C0 ≥ 5 μmol/L and detritus-SPM ≥ 16 mg/L, P removal could exceed 30%. This study highlights two distinctive roles of SPM in regulating P cycling during transport from rivers to lakes. Especially the phytoplankton-SPM to buffer phosphate-limitation during algal blooms should not be ignored, which could provide theoretical references for the mechanism of continued algal blooms in mesotrophic lakes. Graphical abstract: Image, graphical abstract